Correlation of Chest Radiographic findings with Spirometry in Chronic Obstructive Pulmonary Disease (COPD) - Begum, Hawa; Gope, Sudipta; Das, Anjan Kumar; Huq, Syed Maksumul; Rahman, Md. Siddiqur; Hafizullah, Kamruddoza; Parvin, Zohora; Jahan, Most Nasrin (The Insight, 2021)
Objective: Diagnosis of COPD is confirmed on spirometry but diagnosis of emphysema remains problematic. Different modalities have been used in various ways to accurately assess the extent and severity of emphysema. Methods and materials: This cross sectional study was carried out in Radiology & Imaging Department of Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic disorders (BIRDEM), Dhaka during July 2013 to June 2014,on a total of 73 patients with suspicion of COPD to establish diagnostic usefulness of chest X-ray in evaluation of Chronic Obstructive Pulmonary Disease (COPD) and to correlate the findings with spirometry. Result: Majority (39.7%) of the Chronic Obstructive Pulmonary disease (COPD) patients were in 7th decade and the mean age was 62.14±10.59 years. Male to female ratio was almost 3:1.Almost one fourth (24.7%) patients were retired Govt. service, 20.5% were business man and female patients mostly (19.2%) housewives. Almost all male patients were smoker and 47.2% patients belonged to smoking 16-20 pack years. The mean smoking (pack years) was found 17.06±3.47 varies from 11 to 24. The mean forced vital capacity was found 53.42±16.44% and the mean forced expiratory volume in the first second was 31.18±12.06%.The mean FEV1/FVC was found 52.29± 9.82% with range from 39 to 77%. The mean peak expiratory flow was found 31.3±13.09% with range from 9 to 68%.The mean maximal expiration flow rate was found 21.15±11.24% with range from 5 to 49%. More than half (50.7%) of the patients had 1-15 cm height of right dome of diaphragm. The mean height of right dome of diaphragm was found 1.08±0.35cm.The mean right lung length was found 25.15±1.59 cm with range from 22.1 to 27.9cm.Almost two third (65.8%) patients had right dome of diaphragm >7th rib-≤8th rib, 5.5% hand >6th rib - -≤7th rib and 28.8% had >8th rib. Mean than half (54.8%) of the patients had retrosternal space 3.1-3.5 cm and the mean retrosternal space was 3.01±0.52cm. More than two third (68.5%) of the patients hand signs of vascular deficiency (DTRN-S) 2 score and the mean signs of vascular deficiency was found 1.88±0.9cm with range from 0-4 score. Almost forty (39.7%) percent patients had CXR score 7 & the mean CXR score was 7.25±0.98. Forced expiratory volume in the first second and CXR score including FVC and CXR score were statistically significant (p<0.05) among the groups. FEV1/FVC and CXR score were not statistically significant (p>0.05) among the groups. Peak expiratory flow (PEF) and CXR score were statistically significant (p<0.05) among the groups. Maximal expiration flow rate and CXR score were statistically significant (p<0.05) among the groups. A positive significant correlation was r=0.447; (p<0.001) between RSP score with PEF. Significant negative correlation was r=0.428; (p<0.001) between DTRN-S score with FVC, negative significant correlation r=0.304’ (p<0.001) between DTRN-S score with FEV1, negative significant correlation, r=0.247; (p=0.005) between DTRN-S score with FEV1/FVC and negative significant correlation, r=-0.555; (<0.001) between DTRN-S score with PEF. Conclusion: It can be concluded that methodical interpretation of chest radiographs can assess the COPD cases and well correlate with spirometry.